Is There a Need of Harmonization of Postgraduate Dermatology Curriculum in Nepal? - S. Agrawal (Nepal Journal of Dermatology, Venereology & Leprology)
Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.2-4